2020
DOI: 10.1016/j.enbuild.2020.109857
|View full text |Cite
|
Sign up to set email alerts
|

Children's thermal comfort and adaptive behaviours; UK primary schools during non-heating and heating seasons

Abstract: This paper aims to study children's thermal comfort and related Adaptive Behaviours in UK primary schools. The study was carried out in 32 naturally-ventilated classrooms during Non-Heating (NH) and Heating (H) seasons. Alongside collecting environmental data, a self-reported questionnaire and an observation form were employed to record children's thermal comfort and adaptive behaviours. From eight primary schools, 805 children aged 9-11 were surveyed and 1390 questionnaires were collected. Children's Thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 87 publications
0
29
0
1
Order By: Relevance
“…In total, 29 naturally ventilated classrooms in eight primary schools were selected and studied during non-heating (NH) and heating (H) seasons, Table 1. Further details on the selection of the school buildings can be found in an earlier study by authors [52].…”
Section: Buildingsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 29 naturally ventilated classrooms in eight primary schools were selected and studied during non-heating (NH) and heating (H) seasons, Table 1. Further details on the selection of the school buildings can be found in an earlier study by authors [52].…”
Section: Buildingsmentioning
confidence: 99%
“…Window's operation: Windows' operation method affects occupants' practice of ABs; it is shown that manual operation of windows helps to improve IAQ significantly [20,30,40,72,73] and makes people feel more comfortable in manually-controlled buildings [20]. Based on children's physiology, safe windows designed at lower heights are more accessible for children's window operation [20,52]. Therefore, classrooms that provide windows at accessible heights with manual and easy operation for children can potentially increase occupants' practice of ABs.…”
Section: Windowsmentioning
confidence: 99%
See 3 more Smart Citations